Structure and bioactivity of colibactin. - Wernke, Kevin M. (Bioorg Med Chem Lett, 2020)
Colibactin is a secondary metabolite produced by certain strains of bacteria found in the human gut. The presence of colibactin-producing bacteria has been linked to colorectal cancer in humans. Colibactin was first discovered in 2006, but because it is produced in small quantities and is unstable, it has yet to be isolated from bacterial cultures. Here we summarize advances in the field since ~2017 that have led to the identification of the structure of colibactin as a heterodimer containing two DNA-reactive electrophilic cyclopropane residues. Colibactin has been shown to form interstrand cross-links by alkylation of adenine residues on opposing strands of DNA. The structure of colibactin contains two thiazole rings separated by a two-carbon linker that is thought to exist as an α-aminoketone following completion of the biosynthetic pathway. Synthetic studies have now established that this α-aminoketone is unstable toward aerobic oxidation; the resulting oxidation products are in turn unstable toward nucleophilic cleavage under mild conditions. These data provide a simple molecular-level explanation for colibactin’s instability and potentially also explain the observation that cell-to-cell contact is required for genotoxic effects.